Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.17577/ijertv5is070450
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of Under-Reamed Piles in Sand

Abstract: Under-reamed piles are bored cast-in-situ concrete piles having one or more number of bulbs formed by enlarging the pile stem. These piles are best suited in soils where considerable ground movements occur due to seasonal variations, filled up grounds or in soft soil strata. Provision of under reamed bulbs has the advantage of increasing the bearing and uplift capacities. It also provides better anchorage at greater depths. An experimental work was programmed and carried out to understand the behaviour of unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the same way, the enlargements of pile increased the tensile bearing capacity of these piles, making them appropriate for use in the foundation of structures such as centrifuges, piers, various transmission lines, and others [9]. Christopher and Gopinath [10] Study the behavior of under-reamed piles subjected to vertical loads by experimental work in sand soil compared with straight shaft pile, the pile and under-reamed diameter equal to 25 and 75 (mm) respectively. The results show that the under-reamed pile's bearing capacity is higher compared to the straight shaft, about 305%.…”
Section: Applications Of Under-reamed Pilesmentioning
confidence: 99%
“…In the same way, the enlargements of pile increased the tensile bearing capacity of these piles, making them appropriate for use in the foundation of structures such as centrifuges, piers, various transmission lines, and others [9]. Christopher and Gopinath [10] Study the behavior of under-reamed piles subjected to vertical loads by experimental work in sand soil compared with straight shaft pile, the pile and under-reamed diameter equal to 25 and 75 (mm) respectively. The results show that the under-reamed pile's bearing capacity is higher compared to the straight shaft, about 305%.…”
Section: Applications Of Under-reamed Pilesmentioning
confidence: 99%
“…The results showed that the capacity drops off when the bulb angle of the under-ream pile is increased, which is especially apparent at an angle of 75°. Christopher and Gopinath [9] showed that when the space between two bulbs was increased up to 150 mm, an increase in pile capacity occurred. The improvement in load-carrying capacity becomes smaller as the spacing increases.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of the piles in compression and tension was significantly impacted by the number, size, shape, and position of the bulbs [19]. Various studies were also conducted to understand the influence of geometrical features of the underreamed pile on its ultimate capacity by Christopher and Gopinath [20], Shetty et al [21] and Shrivastava and Bhatia [22].…”
Section: Introductionmentioning
confidence: 99%